Juegos lúdicos y su influencia en el desarrollo afectivo de los niños de educación inicial II - Arreaga Arreaga, Joselyn Tatiana (2025)
The present research project is based on the problem that in many cases they are not used with a planned approach to strengthen emotional development. The influence of compliance with academic content and the lack of teacher training in innovative pedagogies can limit the adequate integration of play in the classroom. That is why the main objective is to analyze how playful games contribute significantly to the emotional development of Initial II students. Where the non-experimental design was used as a methodology, followed by the qualitative approach, as a study sample, the collaboration of 2 teachers and 21 toddlers was counted on. Where an interview and observation form were used as data collection tools, through which we helped to collect valuable information on how the teacher plans and effectively integrates these games. As a result, playful games are important tools not only for learning but also for the emotional development of children, these games stimulate curiosity and active participation generating a welcoming and dynamic environment in which it encourages expression and mutual respect. Concluding that playful games, when used correctly, guarantee an enriching educational environment that promotes the well-being of children in their early stages of child development, since social, emotional and cognitive skills are encouraged. Through playful games, children explore their environment, express their emotions and develop creativity, which strengthens the ability to solve problems.